Encontro clínico no modelo biopsicossocial: autopercepção dos acadêmicos de medicina da Pontifícia Universidade Católica de Goiás - CARVALHO, Gélcio Sisteroli de (2010)
Introduction: The Pontifical Catholic University of Goiás pedagogical project for its medical course has stemmed from a thirty year long dream. It came into existence in 2005 following the authorization granted by the National Council of Education after the homologation of the National Curricular Guidelines. The present study shows the need to further investigate the development of assessment processes which are used to identify, follow and materialize changes in medical training. The theory used lies on the possibility of quantifying the medical performance in the patient-physician encounter. Objective: to evaluate some components of the patient-physician encounter based on biopsychosocial model; to create an assessment tool to measure the self-perception of this encounter; to test the effectiveness of this tool in this scenario; and to quantify the category variables of the research in a Pontifical Catholic University of Goiás medical course. Materials and Methods: This was a quantitative, longitudinal and cohort study. The study group presented 39 medical students from 5th Class of the Pontifical Catholic University of Goiás Medical School Course and the investigation was divided into two stages with a year interval between the application of the required academic protocols preceded by a medical semiological conclusion. The dimensions under observation were the following: biomedical, cognitive, ecosystemic, psychological and bioethical. The assessment tool was designed to present 5 dimensions,18 facets and 72 indicators, divided into groups of four alternatives per facet, scaled in degrees 0,1,2 or 3. The higher the degree, the higher the complexity of the biopsychosocial model represented by the software program developed by the researcher called Project 2. Introduction: The Pontifical Catholic University of Goiás pedagogical project for its medical course has stemmed from a thirty year long dream. It came into existence in 2005 following the authorization granted by the National Council of Education after the homologation of the National Curricular Guidelines. The present study shows the need to further investigate the development of assessment processes which are used to identify, follow and materialize changes in medical training. The theory used lies on the possibility of quantifying the medical performance in the patient-physician encounter. Objective: to evaluate some components of the patient-physician encounter based on biopsychosocial model; to create an assessment tool to measure the self-perception of this encounter; to test the effectiveness of this tool in this scenario; and to quantify the category variables of the research in a Pontifical Catholic University of Goiás medical course. Materials and Methods: This was a quantitative, longitudinal and cohort study. The study group presented 39 medical students from 5th Class of the Pontifical Catholic University of Goiás Medical School Course and the investigation was divided into two stages with a year interval between the application of the required academic protocols preceded by a medical semiological conclusion. The dimensions under observation were the following: biomedical, cognitive, ecosystemic, psychological and bioethical. The assessment tool was designed to present 5 dimensions,18 facets and 72 indicators, divided into groups of four alternatives per facet, scaled in degrees 0,1,2 or 3. The higher the degree, the higher the complexity of the biopsychosocial model represented by the software program developed by the researcher called Project 2.Results: Through a circular radial profile with a central point and three areas with crescent spirals graded by differing shades of colors, we have been able to represent the clinical encounter, using the individuals self-perception. The results showed the effectiveness of the software, following a quality control process across all responses. We have used descriptive statistics to mathematically analyze the increase in the study group performance, and compare the responses in percentages in the two stages of the study. We have found a weak association between the category variables (facets) using the Chi-square ratio with the Cramer s-V Coefficient, except for the following facets: Critical Analysis(p 2 = 0,002); Social Health Indicators (p 2 = 0,007); e Health Promotion (p 2 = 0,049). As for individual self-perception, having the facet responses as a reference, 26 subjects (66,7%) showed growth in the formation process; 6 (15,4%) showed decrease and 7 (17,9%) remained unaltered. Conclusion: Through the use of the academic protocol and the biopsychosociallybased patient-physician self-perception assessment tool we have been able to quantitatively assess the academic performance as to knowledge, skills and medical attitudes displayed in the interaction of the physician with the patient. The selfperception assessment tool designed to graphically represent such encounters was put to test and has fulfilled all its objectives. The evaluation of the study group evidentiated some biopsychosocially practices in the pedagogical process used by the Pontifical Catholic University of Goiás Medical School. After a year interval between the stages of the study, an increase was observed in the self-perception of the individuals performance 2,9 times as high as the decrease responses. A long-term application of our findings include opportunities to use this methodology for an on-going self-evaluation of the medical students, provide insights about individual performance in the different stages of the medical training, create a new scenario in the academic portfolios as an evaluation and curricular history resource, and finally adjust the assessment tool so that it could be used by other courses and professionals in the health area working in clinical settings.